EDITORIAL - Ivan Čuk (Science of Gymnastics Journal)
A few days ago SCOPUS published new values for SNIP, IPP and SJR for 2015. In SNIP The Science of Gymnastics has been upgraded and placed in the second quarter of journals. It is a great improvement! In IPP and SJR, we remain in the third quarter. I met and had talks with Hardy Fink, director of FIG Academy, and Prof. Keith Russell, Chairman of the FIG Scientific Commission. We all agree that we need a history section for our sport. Professor Anton Gajdoš, has been writing 'Historical notes' for our journal about important persons in our sport. But there are many important historic documents that should also be made public, such as documents  relating to the foundation of FIG and national federations; how and when national federations entered FIG; documents about previous championships, medals, cups, diplomas; what were the requirements for compulsory and optional exercises and how they looked, etc.